Cardioprotective Effect of Whole Body Periodic Acceleration in Dystrophic Phenotype mdx Rodent - Uryash, Arkady; Mijares, Alfredo; Esteve, Eric; Adams, Jose A.; Lopez, Jose R. (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy (DMD) is characterized by progressive muscle wasting and the development of a dilated cardiomyopathy (DCM), which is the leading cause of death in DMD patients. Despite knowing the cause of DMD, there are currently no therapies which can prevent or reverse its inevitable progression. We have used whole body periodic acceleration (WBPA) as a novel tool to enhance intracellular constitutive nitric oxide (NO) production. WBPA adds small pulses to the circulation to increase pulsatile shear stress, thereby upregulating endothelial nitric oxide synthase (eNOS) and neuronal nitric oxide synthase (nNOS) and subsequently elevating the production of NO. Myocardial cells from dystrophin-deficient 15-mos old mdx mice have contractile deficiency, which is associated with elevated concentrations of diastolic Ca2+ ([Ca2+]d), Na+ ([Na+]d), and reactive oxygen species (ROS), increased cell injury, and decreased cell viability. Treating 12-mos old mdx mice with WBPA for three months reduced cardiomyocyte [Ca2+]d and [Na+]d overload, decreased ROS production, and upregulated expression of the protein utrophin resulting in increased cell viability, reduced cardiomyocyte damage, and improved contractile function compared to untreated mdx mice.